Exploring Students’ English-Speaking Ability Across Proficiency Levels: A Case Study in Indonesian Islamic Boarding School - Mhirda, Maftuch Junaidy; Usadiati, Wahyuningsih; Mafulah, Siti (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
Speaking plays an important role in empowering students learning English as a foreign language to actively engage in various aspects of academic life, such as classroom discussions, presentations, and group projects. However, fluency in English speaking remains a significant challenge for many Indonesian students due to limited exposure to authentic English-speaking environments and insufficient practice opportunities. The aims of this study are to find out the environmental exposure in an Islamic boarding school. Besides, this study also explores the students’ perceptions across proficiency levels in increasing their English-speaking ability in that boarding school. Descriptive qualitative design was used in this study. Observation and interview as the instrument to gain the data were administered in one of Islamic boarding schools in Indonesia. The observation was done to investigate the extent of the English exposure while interview was delivered to 12 students across proficiency levels. The result showed that activities provided by the institution in fostering students’ confidence and fluency are muhadloroh, muhadatsah, and English Day. Those activities play a pivotal role, allowing them to practice speaking in both formal and informal settings. Additionally, peer interactions and consistent exposure to English in daily routines contribute to building communicative competence and reducing language anxiety as the students’ effort in increasing their English speaking ability.